Determination of Mineralization Zones Using Interpretation of IP and RS Data in The GarmabCopper Deposit (South Khorasan province) - Mansour Adelpour; Iraj Rasa; Fariborz Masoudi; Masoud Hosseini (Journal of Economic Geology, 2016)
Introduction The Garmab copper deposit is located northeast of Qaen (South Khorasan province) in the1:100,000 scale map of Abiz in the eastern tectonic zone of Iran. It is hosted by Late Paleocene-Eocene lava flows consisting mainly of andesite, trachy¬andesite, andesite-basalt and basalt lavas, as well as pyroclastic rocks, including tuffs and ignimbrites. The Lut Block has undergone intense magmatic activitywith a variety of geochemical characteristics due to changing tectonic conditions (e.g., compression during subduction followed by tensional conditions; Karimpour et al., 2012; Zarrinkoub et al., 2012). The Lut Block has a great potential for the discovery of new mineral deposits, like the Mahrabad and Khonik porphyry copper-gold deposits (Malekzadeh shafarodi, 2009), the Dehsalam porphyry copper deposit (Arjmandzadeh, 2011), high sulfidation epithermal gold deposits such as Chah Shalghami (Karimpour, 2005) and IOCG deposits such as Kuh-E-Zar and Qaleh Zari (Mazlomi et al., 2008).